2019
DOI: 10.1021/acsabm.9b00842
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of Ratiometric Near-Infrared Aza-BODIPY-Based Fluorescent Probe for in Vivo Imaging of Endogenous Hydrogen Peroxide

Abstract: Precise in vivo tracking of hydrogen peroxide is still challenging due to its dynamic complexity and intrinsic background interference. Herein, we describe a rational design strategy to construct asymmetric aza-boron-dipyrromethane derivative (BODIPY)-based ratiometric probes for in vivo tracking H 2 O 2 , which are composed of a near-infrared aza-BODIPY core, active targeting group, and H 2 O 2 -specific recognition unit. We take advantage of two terminal functionalized conjunctions in the bis-condensed aza-B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 41 publications
0
26
0
1
Order By: Relevance
“…Luminescent molecules with bright and deep-red emission generally are favorable in bio-imaging applications since they hold the advantages of non-invasiveness, deep penetration depth, superior anti-photobleaching capability, and low photodamage to cell or tissue. 56,57 On the other hand, researchers have found that lipid droplets (LDs), used to be considered only as inert reservoirs of lipids for energy storage, have an essential influence on the normal function of cells. 58 The abnormalities of LDs will lead to several like chronic hepatitis and liver cirrhosis etc.…”
Section: Resultsmentioning
confidence: 99%
“…Luminescent molecules with bright and deep-red emission generally are favorable in bio-imaging applications since they hold the advantages of non-invasiveness, deep penetration depth, superior anti-photobleaching capability, and low photodamage to cell or tissue. 56,57 On the other hand, researchers have found that lipid droplets (LDs), used to be considered only as inert reservoirs of lipids for energy storage, have an essential influence on the normal function of cells. 58 The abnormalities of LDs will lead to several like chronic hepatitis and liver cirrhosis etc.…”
Section: Resultsmentioning
confidence: 99%
“…Fluorescence detection technique is one of the effective and convenient imaging tools to identify the target biomarkers in bio‐system. [ 11‐20 ] Compared to other methods, fluorescence technique shows higher sensitivity, simple operation process and non‐destructive imaging capability. [ 21‐24 ] To date, various fluorescent probes especially those with long‐wavelength emission have been synthesized for H 2 O 2 detection, as summarized in Table S1.…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…[35] These effectsc an be enlarged through the peripherical arylationo ft he aza-BODIPYc hromophoric core. [32][33][34] Recently,e fficient and long-lastingf luorescent and laser emission in the target red/NIR spectralr egion have been recordedf rom polyarylateda za-BODIPYs under drastic pumping conditions. [36] In this work, we report for the first time to the best of our knowledge red/NIR TADF emitters based on heavy-atom-free aza-BODIPY derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the simple replacement of the meso ‐methine group at the BODIPY core by an electronegative nitrogen atom induces a pronounced bathochromic shift of both the absorption and emission transitions as well as a drastic decrease of the energy gap between excited singlet and triplet states without promoting phosphorescence emission [35] . These effects can be enlarged through the peripherical arylation of the aza‐BODIPY chromophoric core [32–34] . Recently, efficient and long‐lasting fluorescent and laser emission in the target red/NIR spectral region have been recorded from polyarylated aza‐BODIPYs under drastic pumping conditions [36] …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation